2012
DOI: 10.1142/s179398441241005x
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis Pathways for Nucleic Acid Therapeutics

Abstract: The development of nanoscale delivery vehicles for siRNAs is a current topic of considerable importance. However, little is understood about the exact trafficking mechanisms for siRNA-vehicle complexes across the plasma membrane and into the cytoplasm. While some information can be gleaned from studies on delivery of plasmid DNA, the different delivery requirements for these two vehicles makes drawing specific conclusions a challenge. However, using chemical inhibitors of different endocytosis pathways, studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…For this mode of trafficking, it was thought that when cells were exposed to nanoparticles carrying siRNA that following endosomal acidification the result was lysosomal osmotic swelling and rupture, leading to the release of its contents into the cytosol (protonsponge effect). 5,41 Several studies have reported this mode of internalization and trafficking to be an efficient route for nanoparticles to release siRNA into the cytoplasm. 40−42 However, recent studies have suggested that siRNA release from nanoparticles may be more complex and involve multiple internalization and trafficking processes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this mode of trafficking, it was thought that when cells were exposed to nanoparticles carrying siRNA that following endosomal acidification the result was lysosomal osmotic swelling and rupture, leading to the release of its contents into the cytosol (protonsponge effect). 5,41 Several studies have reported this mode of internalization and trafficking to be an efficient route for nanoparticles to release siRNA into the cytoplasm. 40−42 However, recent studies have suggested that siRNA release from nanoparticles may be more complex and involve multiple internalization and trafficking processes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The physicochemical properties of nanoparticles including, size, shape, and surface charge can have a major influence on the mode of internalization and intracellular trafficking. , Accumulating evidence shows that different modes of endocytosis can lead to different intracellular trafficking of nanoparticles within the cell, which can impact transfection efficiency. , Intracellular trafficking is a dynamic process and is responsible for transporting internalized molecules to different subcellular locations. , For example, nanoparticles that are internalized via a clathrin-dependent endocytic pathway can be transported from early endosomes to lysosomes. For this mode of trafficking, it was thought that when cells were exposed to nanoparticles carrying siRNA that following endosomal acidification the result was lysosomal osmotic swelling and rupture, leading to the release of its contents into the cytosol (proton-sponge effect). , Several studies have reported this mode of internalization and trafficking to be an efficient route for nanoparticles to release siRNA into the cytoplasm. However, recent studies have suggested that siRNA release from nanoparticles may be more complex and involve multiple internalization and trafficking processes. Gilleron et al demonstrated that the internalization and trafficking of lipid nanoparticles is cell-type dependent and can use both clathrin-mediated endocytosis and micropinocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…Efficient transfection and release of Bcl-2 AONs in MCF-7 cells was effective for all systems except for the K-PA assembly, presumably due to poor AON binding with only a single lysine available for complementary pairing. Transport assays conducted in the presence of uptake inhibitors 655 demonstrated that AON delivery with the K-PA/AON and the R 4 -PA/AON complexes were not inhibited by any of the assessed inhibitors, suggesting a non-endocytotic pathway for internalization. Delivery with the R 8 -PA and KRSR-PA/AON complexes were found to be dynamin-mediated and interestingly, coassembled R 8 -PA/KRSR-PA/AON complexes were found to be mediated by dynamin, clathrin-mediated endocytosis, and caveolae-mediated endocytosis internalization pathways, indicating the complex effects of PA formulation on transport mechanism.…”
Section: Peptide/biopolymer Hybridsmentioning
confidence: 95%
“…Uptake inhibitors were used to study the mechanisms involved in the internalization of PAs decorated with CPPs and heparin binding sequences (Figure ). Amiloride, dynasore, chlorpromazine, and nystatin were used to inhibit macropinocytosis, dynamin-dependent pathway, clathrin-mediated endocytosis, and caveolae-mediated endocytosis, respectively . The internalization of K-PA and R 4 -PA was not inhibited with any of the chemical inhibitors used, which strongly indicates that the internalization was via a nonendocytotic pathway and probably through direct translocation.…”
Section: Resultsmentioning
confidence: 99%